ICE BREAKING DALAM PEMBELAJARAN MATEMATIKA - Nur Saidah Arifin (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
Learning feels boring is something that is not uncommon when in class and learning takes place. That's why a teacher needs to foster student interest with appropriate teaching and learning strategies, one of which is ice breaking. Researchers did this to find out the application and relationship between the application of Ice Breaking and attracting students' attention and interest. The process in this research carried out a qualitative method, namely a technique that collects data through analytical documentation from several previous journals and then describes it in a systematic and structured manner. The research conducted showed that: (1) Ice breaking can be carried out in all subjects, both formal and non-formal education. And also ice breaking can be collaborated with other learning models or strategies. (2) Applying ice breaking can attract attention and interest in learning, increase motivation in learning, enthusiasm and the results obtained from student learning will be better, (3) Ice breaking has benefits that can be applied to divert feelings of boredom, saturation and sleepiness when learn very simple things.